PENGUATAN KOMPETENSI PUBLIC SPEAKING BERBASIS SIMULASI UNTUK MENINGKATKAN KESIAPAN KARIR MAHASISWA - Dewirahmadanirwati Dewirahmadanirwati; Ridha Hasnul Ulya; Ineng Naini; Amrullah Amrullah; Afrida Afrida; Asmawati Asmawati (ASOSIASI IDEBAHASA KEPRI, 2026)
Speaking skills are crucial for students to face academic and professional demands in the global era; however, low self-confidence and difficulties in delivering ideas systematically remain prevalent. This community service activity aims to enhance students' communication competence through the